Pengaruh Pangan Lokal Dan Pola Asuh Makan Terhadap Kejadian Stunting Pada Balita 6- 24 Bulan Di Kota Bandung - Lolan, Yosef; Adni Fauzia, Diah (Jurnal Kesehatan Mahardika, 2023)
Background: A good eating pattern is reflected in the better food intake given to toddlers. Local wisdom food in this study is tubers. Local food has many advantages, such as: food safety that is guaranteed or has no side effects (safe food and food security), easy to obtain at low cost or no cost (economic efficient), easy to cultivate, good nutritional value and can increase household income (health economy).. Purpose: to determine the effect of local food and food parenting patterns in toddlers on the incidence of stunting in the city of Bandung. Method: This type of research is a descriptive-analytic exploratory study using a cross-sectional design. The sample in this study was 235 mothers who have toddlers who live in the city of Bandung. The sampling technique used is nonprobability using purposive sampling. Results: This study shows that the variables associated with the incidence of stunting are: Father's education with a P-value of 0.034, local food processing for toddlers gets a p-value of 0.022 and parenting style to eat nutritious food for toddlers with a p-value of 0.001. Conclusion: The risk factors for stunting in toddlers are local food processing and parenting patterns of nutritious food.